The High-k Solution. - Bohr, M.T (IEEE spectrum)
The Intel's Core 2 microprocessors, based on the latest 45-nanometer CMOS process technology have more transistors and run faster and cooler than microprocessors fabricated with the previous, 65-nm process generation. For compute-intensive music, video, and gaming applications, users will see a hefty performance increase.